A Production and operations management study on General Electric and Philippine Electrical Manufacturing Company (GE & PEMCO) - Buenaventura, Luis III; Del Rosario, Ryan Kenneth; Nepomuceno, Larissa (Diliman, Quezon City College of Engineering, 2003)
General Electric and Philippine Electrical Manufacturing Company produces incandescent and fluorescent lamps. It is the goal of the company to maintain and enhance the quality image of its products by meeting and satisfying the quality expectations and needs of their customers. The manufacturing and the business process of the company were assessed in line with the topics of Production and Operations Management. In a general perspective, GE and PEMCO, was observed to typify an assembly plant, wherein operations are characterized by high volume and low variety production. The production system is generally organized around the product and the organizational structure forms that of a vertical arrangement, which is also appropriate for the type of production mentioned. The objectives of this paper are to perform an analysis on the production systems of the company and to be able to come with feasible recommendations aiming to improve the system. Specific details were thus presented so as to establish possible problem areas in the company, which may be addressed by this paper. Initially, the streamline diagnostic tool was applied for the general problem identification. An Ishikawa diagram was then applied so as to identify the immediate causes of the problem. It was pointed out that the opportunity cost, or the lost opportunities in terms the possible cost savings or profit was indeed the general problem. The general causes to the problem of opportunity cost was then identified to be the long warm-up times necessary in setting up machines, the additional storage expenses, and the need for outsourcing. To address these concerns, the team focused on the fundamental problems of the root causes of these. The three fundamental problems were then identified to be 1) Inaccurate Demand Forecasts, 2) Insufficient Storage Space, 3) Low Capacity Machines. To address the problem of Inaccurate Demand Forecasts, the team proposed that the Marketing/Sales employees be given training programs in forecasting. An alternative forecasting technique was proposed, the exponential technique with a smoothing constant alpha of 0.5, which was justified to have improvements, pertaining to the minimization of deviations and frequency of excess inventories. The team also suggested establishing a special marketing team to aid in coming with more accurate forecasts for the company. To address the problem of Insufficient Storage Space, a proposal as how to improve finished goods distribution was presented. A recommendation with regard to expanding the storage facility was also presented with the aid of the Payback Period Method from Engineering Economy. And to address the problem of Low Capacity Machines, it was recommended that the company should purchase new equipment and this was also presented through the aid of the Payback Period Method. The alternative recommendation for this was to apply a more stringent maintenance procedure and a proposed maintenance schedule was presented.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: General Electric; Philippine Electrical Manufacture; Electric utilities; Production engineering